Heck reaction of alkyl halides and α-selective heck reaction of styrenes - Zou, Yinjun (2014)
My graduate study has been focused on the development of transition metal-catalyzed reactions, especially Pd-catalyzed coupling reactions. In this thesis, we described two catalytic systems that solved challenging problems in the intermolecular Heck reaction.